Exploring photochemistry of p-bromophenylsulfonyl, p-tolylsulfonyl and methylsulfonyl azides by ultrafast UV-pump–IR-probe spectroscopy and computations. Issue 12 (7th March 2016) - Kuzmin, A. V.; Neumann, C.; van Wilderen, L. J. G. W.; Shainyan, B. A.; Bredenbeck, J.
Abstract : The photochemistry of three sulfonylazides was studied by femtosecond time-resolved infrared (TRIR) spectroscopy and quantum chemical computations. Abstract : The photochemistry of p -bromophenylsulfonyl azide (BsN3 ), p -tolylsulfonyl azide (TsN3 ) and methylsulfonyl azide (MsN3 ) was studied by femtosecond time-resolved infrared spectroscopy with CH2 Cl2 and CCl4 as solvents along with quantum chemical calculations. The photolysis of these azides after 267 nm light excitation leads to the population of each respective azide S1 excited state. Decay of the S1 excited state gives rise to singlet nitrene formation. In the case of BsN3, the decay was found to correlate with the formation of a pseudo-Curtius photoproduct (PCP) BrC6 H4 NSO2 . Transient electronic ground states of the three azides on their way to singlet nitrenes and PCPs were shown by locating the corresponding transition states on the potential energy surfaces. The lifetime of singlet 1 (BsN) and 1 (TsN) nitrenes is τ S = ∼20 ps in CH2 Cl2 and ∼700 ps in CCl4 . Singlet 1 (MsN) was not detected. Due to fast intersystem crossing (ISC), singlet nitrenes are converted into the triplet spin isomers lying lower in energy, the formation time constants being equal to the corresponding singlet nitrene lifetime. The formation of 3 (MsN) was shown and the formation time constant in CH2 Cl2 was found to be τ ISC = 34 ± 3 ps. Internal conversion of the S1 excited state to the ground state of the azide was low ( Φ ≈ 0.15) for BsN3 and TsN3 and was not found in the case of MsN3 .